2014
DOI: 10.1177/0892705713519121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various knitting techniques on mechanical properties of biaxial weft-knitted thermoplastic composites

Abstract: Within the scope of experiments, five kinds of biaxial weft-knitted (BWK) fabrics with various knitting techniques (plain, interlock, tuck, tuck-miss, and interlock2) were used as reinforcement systems to fabricate thermoplastic composites with polypropylene (PP) resin yarn. Then, the final composite became BWK composites with various knitting types. The mechanical properties of composites were investigated by conducting tensile, three-point bending, and three-point bending impact tests on specimens. In all sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…2 This is why, their applications are increasingly growing in various industries such as aerospace, transportation and construction. 3 Among the different textile structures, weft-knitted fabrics 4,5 demonstrate high deformability that makes them suitable in fabricating the complex-shaped composite parts. 6 This intrinsic flexibility is induced by the yarn interlooping which creates inferior mechanical properties in comparison to woven fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…2 This is why, their applications are increasingly growing in various industries such as aerospace, transportation and construction. 3 Among the different textile structures, weft-knitted fabrics 4,5 demonstrate high deformability that makes them suitable in fabricating the complex-shaped composite parts. 6 This intrinsic flexibility is induced by the yarn interlooping which creates inferior mechanical properties in comparison to woven fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…After performing the tension, in-plane shear and flexure tests, they concluded that the warp knitted material was stiffer and marginally stronger when compared to the woven material. Demircan et al 17 investigated the effect of the various knitting techniques on the mechanical properties of the biaxial weft-knitted thermoplastic composites. They found that the tensile, three-point bending, and three-point bending impact properties of the thermoplastic composites with the commingled yarns could be improved by changing the knitting techniques.…”
Section: Introductionmentioning
confidence: 99%
“…By combining a commingling method of reinforcement and thermoplastic filaments with a weftknitting technology, pre-mixed dry semi-products may present a promising alternative to reduce cycle-time. In particular, biaxial weft-knitted fabrics (BWKF) are potential candidates to obtain composite parts with a complex geometry at a reduced cycle-time (Li and Bai, 2009;Risicato et al, 2014;Demircan et al, 2015). However, the better understanding of the consolidation mechanism is still required to optimize the impregnation quality of obtained products.…”
Section: Introductionmentioning
confidence: 99%